PENGARUH SISTEM INFORMASI MANAJEMEN RUMAH SAKIT TERHADAP KINERJA KARYAWAN - Nadya Faradhifa (LPPM Universitas Awal Bros, 2020)
Employee performance is the result of the achievement of a worker in completing the tasks and roles performed in an organization. All actions taken by employees in carrying out their work are the result of the employee's performance. There are several factors that are considered to influence employee performance, including management information systems and the work environment. The hospital management information system is an operational system that is the main component in the realization of good service in hospitals, namely data management. As we know in this day and age, with the available technology it can make it easier for employees to carry out their duties so as to avoid mistakes which of course cannot be avoided when doing work that will have a very large impact Method: literature review is carried out based on issues, methodology. Of the 2 studies used, 1 The method used is by distributing questionnaires to employees by conducting statistical associative analysis tests to see how the influence between the application of management information systems on employee performance and collecting data on complaints on employee performance 1 other research is using data collection methods. Field research (ground research. Results: based on the research. From the results of the calculation of the coefficient of determination, it can be concluded that the effect of variable X (Management Information System) on variable Y (Performance) has a very strong relationship because it has an interval value of 88%, the remaining 12% is influenced by other factors not studied.